PERANCANGAN DAN PENGEMBANGAN SISTEM INFORMASI TUGAS AKHIR TERINTEGRASI DENGAN PENILAIAN KURIKULUM BERBASIS OUTCOME-BASED EDUCATION (OBE) - Feri Irawan; Berta Erwin Slam; Nolan Efranda; Rifaldi Herikson; Novrizal Fattah Fahmitra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The implementation of an Outcome-Based Education (OBE) curriculum in higher education requires an information system capable of integrating academic processes with learning outcome assessments in a structured and transparent manner. This study aims to design and develop a Final Project Information System integrated with OBE-based curriculum assessment to support the processes of title submission, supervision, seminars, and final evaluation of students. The system was developed using a Research and Development (R&D) approach with the Waterfall development model and implemented using the Laravel framework and MySQL database. Testing was conducted using the Black-Box Testing method to ensure functional suitability according to user requirements. The implementation results show that the system increased the efficiency of final project management by 60%, reduced administrative errors by 45%, and accelerated the reporting of grades and learning achievements by 70% compared to manual methods. Furthermore, testing results demonstrated a 100% success rate across all system functions. Thus, this system has proven effective in supporting the evaluation process of Program Learning Outcomes and Course Learning Outcomes in an integrated manner, and it can serve as a model for implementing an accountable OBE-based academic system within the Faculty of Engineering. Keyword: Final Project Information System; Outcome-Based Education; Curriculum Assessment; Learning Outcomes Evaluation; Academic System Abstrak: Penerapan kurikulum berbasis Outcome-Based Education (OBE) di pendidikan tinggi menuntut tersedianya sistem informasi yang mampu mengintegrasikan proses akademik dengan asesmen capaian pembelajaran secara terstruktur dan transparan. Penelitian ini bertujuan untuk merancang dan mengembangkan Sistem Informasi Tugas Akhir yang terintegrasi dengan penilaian kurikulum berbasis OBE guna mendukung proses pengajuan judul, bimbingan, seminar, dan penilaian akhir mahasiswa. Sistem dikembangkan menggunakan pendekatan Research and Development (R&D) dengan model pengembangan Waterfall, serta diimplementasikan menggunakan framework Laravel dan basis data MySQL. Pengujian dilakukan menggunakan metode Black-Box Testing untuk memastikan kesesuaian fungsi dengan kebutuhan pengguna. Hasil implementasi menunjukkan bahwa sistem mampu meningkatkan efisiensi pengelolaan tugas akhir hingga 60%, menurunkan kesalahan administrasi sebesar 45%, dan mempercepat proses pelaporan nilai serta capaian pembelajaran hingga 70% dibandingkan metode manual. Selain itu, hasil pengujian menunjukkan tingkat keberhasilan 100% pada seluruh fungsi sistem. Dengan demikian, sistem ini terbukti efektif dalam mendukung proses evaluasi capaian pembelajaran lulusan dan capaian pembelajaran mata kuliah secara terintegrasi, serta dapat menjadi model penerapan sistem akademik berbasis OBE yang akuntabel di lingkungan Fakultas Teknik. Kata kunci: Sistem Informasi Tugas Akhir; Outcome-Based Education; Penilaian Kurikulum; Evaluasi Capaian Pembelajaran; Sistem Akademik